Panama : Report on the Observance of Standards and Codes-Data Module. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2021)
Panama's statistical system is well established by a legal framework that generally provides the necessary authority for the collection and compilation of statistics. Panama has a well-developed macroeconomic statistical system and the government recognizes the importance of good statistics for policy and investment decisions. This Report on the Observance of Standards and Codes (ROSC) is a follow-up to the Panama ROSC issued in 2006. Since 2006, Panama has acted upon a number of the recommendations of the previous ROSC, has passed and implemented new statistical legislation, created the National Statistical Institute and enhanced its statistical compilation and dissemination practices. This report assesses the current state of the statistical system and makes a number of recommendations related to future developments that will further enhance the statistical system. The legal framework assigns responsibility for the socio-economic statistics to the Comptroller General of the Republic of Panama (CG), which is subsequently delegated to the National Statistical Institute (INEC). Among other social and economic data INEC compiles and disseminates national accounts, consumer price index (CPI), government finance, and external statistics. The MEF in collaboration with INEC also compiles and disseminates fiscal statistics. Given Panama's long history of dollarization and absence of a central bank, there is no assignment of responsibility for compiling and disseminating a complete set of monetary and financial statistics. Instead, the Superintendency of Banks of Panama (SBP) produces banking sector statistics in line with its functions. Consequently, statistical practices for some elements of the DQAF do not apply to this sector (Box 1). Opportunities exist for improving the methodological basis and source data for most datasets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Panama